Spatial–temporal patterns of fish trophic guilds in a freshwater river wetland ecosystem of northeastern China - Xu Sun; Kai Wang; Ge Zhang; Han Ren; Hongxian Yu (Ecology and Evolution, 2024)
Abstract Muling River, situated amidst cultivated lands in Heilongjiang Province, northeastern China, has long been subjected to sand‐digging activities, resulting in severe damage to its riverbed. However, little research has been conducted on the impact of this disturbance on the status of fish community structure and trophic guilds in this river. In this study, environmental factors, fish community structure, and fish trophic guild biomass distribution patterns from the Muling River basin were investigated among seasons (spring, summer, and autumn) and sections (upper, middle, and lower stream) in 2015 and 2017. During the six sampling times periods, 46 species of five orders and 12 families of fish were classified into seven trophic guilds. Fish species number and biomass were higher upper reaches of the watershed. The insectivores (16.26%), phytoplanktivores (10.09%), benthivores (40.17%), and omnivores (11.86%) were the dominant trophic guilds. We found that fish trophic guilds biomass and environmental factors such as transparency, water depth, pH value, total phosphorus, and chemical oxygen demand were highest in the upper section compared to other sections. Variation partitioning revealed that fish trophic guilds biomass was influenced more by environmental factors (61.2%), followed by section (0.7%) and season (0.1%). Partial RDA ordination showed that fish trophic guilds were positively correlated with water depth and transparency, while negative with turbidity. This study underscores the importance of considering trophic guilds of freshwater fishes to inform management strategies in regions experiencing significant environmental change.